The Effect of Work Interest Typology Approach to Improve Positive Attitudes in Inclusive School Teachers: Pengaruh Pendekatan Tipologi Minat Kerja untuk Meningkatkan Sikap Positif pada Guru Sekolah Inklusi - Savira, Siti Ina; Satwika, Yohana Wuri; Khoirunnisa, Riza Noviana; Darmawanti, Ira; Humaida, Venna Arzika (Universitas Muhammadiyah Sidoarjo, 2024)
One of the challenges faced by teachers in inclusion schools is directing students according to students' interests and talents. This challenge has an impact on teachers' reluctance to put in more effort to help students with disabilities find appropriate talents and interests. This research is a descriptive quantitative research, which aims to change the attitude of inclusive school teachers using a typology approach to student work interests. The approach used is a typology of work interests developed from Holland's vocational-personality theory. This research was carried out on teachers in one of the private high school inclusive schools in Surabaya. The results showed a change in teachers' attitudes towards students with disabilities as shown by the desire to learn and apply new things that can help students with disabilities.